The turbine driven rotor concept - A new vision for helicopter propulsion - Buysschaert, F.; Newman, S.; Walker, S.; Antoine, H.; Hendrick, P. (My University, 2014)
The TDR-helicopter concept is a helicopter configuration with no mechanical transmission, using coaxial rotors driven by a Ljungström turbine. This configuration offers reduced helicopter complexity and weight. Three TDR-helicopter cycles are proposed and examined thermodynamically. The piston engine cycle, using Avgas and diesel, and the turboshaft engine cycle exhibit design cycle specific fuel consumptions that are competitive with conventional helicopters, even though being limited by the Ljungström turbine bearing temperature. However, the turboshaft engine cycle is less attractive because of the need for heat exchangers and the loss of the exhaust gas mass flow. The turbofan cycle does not suffer from this problem and offers the potential to outperform the conventional helicopter, while offering propulsive force in addition.